2012
DOI: 10.1002/ece3.399
|View full text |Cite
|
Sign up to set email alerts
|

Deglaciation explains bat extinction in the Caribbean

Abstract: Ecological factors such as changing climate on land and interspecific competition have been debated as possible causes of postglacial Caribbean extinction. These hypotheses, however, have not been tested against a null model of climate-driven postglacial area loss. Here, we use a new Quaternary mammal database and deep-sea bathymetry to estimate species–area relationships (SARs) at present and during the Last Glacial Maximum (LGM) for bats of the Caribbean, and to model species loss as a function of area loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
1
27
1
Order By: Relevance
“…Proportion of present and fossil localities occurring within karst (i.e., karst buffer = 0 km) and at increasing 5 km distances away from karst (i.e., karst buffer = 5, 10, 15, 20, 25, and >25 km contraction from LGM to the present. This supports the hypothesis that loss of land area had a negative effect on populations of bat in the Caribbean (Dávalos and Russell, 2012). However, when corrected for island area, changes in RRS are small for land areas that were not affected by sea level change over time, such as the Greater Antilles, and in all species indicate a range expansion from past to present (table 1).…”
Section: Pteronotus Parnellii Pteronotus Quadridenssupporting
confidence: 75%
See 1 more Smart Citation
“…Proportion of present and fossil localities occurring within karst (i.e., karst buffer = 0 km) and at increasing 5 km distances away from karst (i.e., karst buffer = 5, 10, 15, 20, 25, and >25 km contraction from LGM to the present. This supports the hypothesis that loss of land area had a negative effect on populations of bat in the Caribbean (Dávalos and Russell, 2012). However, when corrected for island area, changes in RRS are small for land areas that were not affected by sea level change over time, such as the Greater Antilles, and in all species indicate a range expansion from past to present (table 1).…”
Section: Pteronotus Parnellii Pteronotus Quadridenssupporting
confidence: 75%
“…In contrast, only about 18% of Caribbean bats became extinct during the same period (Pregill and Olson, 1981;Morgan, 2001;Dávalos and Turvey, 2012). Changes in island area due to rising sea level and concomitant changes in cave availability due to flooding and loss of roosting habitats after the PHT have been proposed to explain Caribbean bat extinctions (Morgan, 2001;Dávalos and Russell, 2012). However, recent evidence from radiocarbon chronology has indicated that many bat fossils in the Caribbean are younger than previously thought, and that many species of bat survived the PHT by 5-7 ky (Soto-Centeno and Steadman, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…little is known about these extinct taxa other than that they occurred sympatrically with congeners, suggesting that diversity of sympatric mormoopid communities may have been even greater in the Pleistocene than it is today. a recently discovered correlation between loss of species and loss of island area due to rising sea levels since the last glacial maximum (lGM) suggests that climate change may have been one of the major drivers of extinction of caribbean bats since the Pleistocene (Dávalos and Russell, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…in the case of Lasiurus insularis, extant populations occur today only in cuba, but fossils of this species are known from both cuba and Hispaniola (Morales and Bickham, 1995;Morgan, 2001;Simmons, 2005;Dávalos and turvey, 2012;nuñez novas and león, 2011). Reasons for the local or regional extinctions of these taxa could have included a variety of factors including competition with other bat species (koopman and Williams, 1951;Williams, 1952), natural habitat changes (e.g., increased xerification; Pregill and olson, 1981), deforestation (Gannon et al, 2005), flooding of roost caves due to sea-level changes (Morgan, 2001;Dávalos and turvey, 2012), or more complex ecological factors associated with reduced island areas after the lGM (Dávalos and Russell, 2012). in the case of Lasiurus insularis, a tree-roosting species (Silva taboada, 1979), anthropogenic deforestation and stochastic events such as hurricanes might have played a significant role; in the case of Mormoops and Pteronotus species, which rely on caves for roosts, rising sea levels and cave flooding seem more likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation